UJI KOMBINASI PUPUK ORGANIK DAN ANORGANIK DALAM POLA LEISA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SORGUM LOKAL PADA LAHAN MARGINAL - Leomo, Sitti; Sutariati, Gusti Ayu Kade; Agustina, Agustina (Jurnal Agroteknos, 2012)
The  experiment  was  aimed  to  know     the  effect  of  combination  of  organic  and anorganic  fertilizers  on  growth  and  yield  of  local  sorghum  crops  on  dry  land.  The experiment    was  conducted  in  Kambu  District  Poasia  and  Agrotechnology  Laboratory, Faculty of Agriculture University of Haluoleo, from August to December 2011. The experiment was arranged on randomized block design (RBD), which consisted   of 7 treatments namely: control (A), 5 tons ha-1 of organic fertilizer (B), anorganic fertilizer (200 kg ha-1 urea, 100 kg ha-1 SP36 and 50 kg ha-1 KCl) (C), organic + anorganic fertilizer full recommended dosage (D), organic fertilizer +1/2 recommended dosage of anorganic fertilizer (E), organic fertilizer + ¼ recommended dosage of  anorganic fertilizer (F) and organic fertilizer + 1/8 recommended dosage of anorganic fertilizer (G). Each treatment was repeated 3 times, therefore  overall there were  21 experimental units. Data obtained were analyzed using  analysis of  variance and  followed by  Duncan’s Multiple Range Test. The research results showed that the combination of organic and anorganic fertilizers provided a significant influence on growth and yield of sorghum crops. Treatment of organic fertilizer + ½ recommended dosage of anorganic fertilizer (organic fertilizer 5 ton ha-1 + anorganic fertilizer 100 kg ha-1 Urea, 50 kg ha-1 SP36dan 20 kg ha-1 KCl) gave better effects on the observed variables: plant height, stem diameter, leaf number, leaf area, dry weight of plant biomass, panicle length, fresh weight of panicle, grain weight and the weight of 1000 seeds of sorghum. Keywords: combination of organic and anorganic fertilizers, rhizobakteria, sorghum